2009
DOI: 10.1161/circulationaha.108.813576
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Regulation of Myocardial microRNAs and Messenger RNA in Human Cardiomyopathy and Reversal of the microRNA Signature by Biomechanical Support

Abstract: Background-Much has been learned about transcriptional control of cardiac gene expression in clinical and experimental congestive heart failure (CHF), but less is known about dynamic regulation of microRNAs (miRs) in CHF and during CHF treatment. We performed comprehensive microarray profiling of miRs and messenger RNAs (mRNAs) in myocardial specimens from human CHF with (nϭ10) or without (nϭ17) biomechanical support from left ventricular assist devices in comparison to nonfailing hearts (nϭ11). Methods and Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
256
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(284 citation statements)
references
References 52 publications
18
256
0
6
Order By: Relevance
“…The down-regulation of the myomir mir-1-1(4) therefore supports a myogenic dedifferentiation in human HF. The reported regulation in human HF and fetal myocardium, however, has been controversial, including observations of increased mir-1-1(4) expression (11,14). Furthermore, we only detected marginal differences in miRNA expression between ICM and DCM hearts and no differences before and after LVAD support, both of which are supported by another recent RNAseq study (17), but contrasted with a microarray-based study reporting more dramatic differences in their comparison of hearts before and after LVAD treatment (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The down-regulation of the myomir mir-1-1(4) therefore supports a myogenic dedifferentiation in human HF. The reported regulation in human HF and fetal myocardium, however, has been controversial, including observations of increased mir-1-1(4) expression (11,14). Furthermore, we only detected marginal differences in miRNA expression between ICM and DCM hearts and no differences before and after LVAD support, both of which are supported by another recent RNAseq study (17), but contrasted with a microarray-based study reporting more dramatic differences in their comparison of hearts before and after LVAD treatment (14).…”
Section: Discussionmentioning
confidence: 99%
“…The reported regulation in human HF and fetal myocardium, however, has been controversial, including observations of increased mir-1-1(4) expression (11,14). Furthermore, we only detected marginal differences in miRNA expression between ICM and DCM hearts and no differences before and after LVAD support, both of which are supported by another recent RNAseq study (17), but contrasted with a microarray-based study reporting more dramatic differences in their comparison of hearts before and after LVAD treatment (14). It is conceivable that distinctive myocardial miRNA changes reflecting heterogeneous genetic or environmental etiologies as well as the myocardial response to pharmacologic and nonpharmacologic therapies exist and that these changes are detectable at early stages of HF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some authors 22,27,28 observed a reduction in miR-1 in ischemic and non-ischemic dilated cardiomyopathy, others observed an increase 21,29 . Han et al 25 suggest the possibility that miR-1 is reduced in hypertrophy, but returns to normal or above normal when the condition progresses to HF.…”
Section: Micrornas and Heart Failurementioning
confidence: 98%
“…It regulates the expression of the beta myosin heavy chain, resulting in the enhancement of myocardial oxygen metabolism and tolerance (24). It has also been demonstrated that the expression levels of miR-499 exhibit a significant change in certain heart diseases, including AMI (25,26).…”
Section: Plasma Levels Of Mir208b (A) and Mir499 (B) Were Significantmentioning
confidence: 99%